Teaching at rehabilitation schools: An exploration of approaches - Noor Insyiraah Abu Bakar, Abdul Talib Mohamed Hashim, Azlina Abu Bakar @ Mohd, Mohd Muslim Md Zalli, Izazol Idris (Tanjung Malim, 2024)
Teaching at rehabilitation schools: An exploration of approaches by Noor Insyiraah Abu Bakar, Abdul Talib Mohamed Hashim, Azlina Abu Bakar @ Mohd, Mohd Muslim Md Zalli, Izazol Idris